47=(7z-3)-(4z-11)

Simple and best practice solution for 47=(7z-3)-(4z-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 47=(7z-3)-(4z-11) equation:


47=(7z-3)-(4z-11)

We simplify the equation to the form, which is simple to understand
47=(7z-3)-(4z-11)

Remove unnecessary parentheses
47=7z-3-(4z-11)

Remove unnecessary parentheses
47=7z-3-4z+11

We move all terms containing z to the left and all other terms to the right.
-7z+4z=-3+11-47

We simplify left and right side of the equation.
-3z=-39

We divide both sides of the equation by -3 to get z.
z=13

See similar equations:

| -6x-167=9x+88 | | 6u=96 | | -6x-167=88 | | 2x^2+8x+31=0 | | -x-2/7=x+1/6+4/7 | | 12x-18=10x+10 | | 5c-4b= | | 4n+1-5n=6n+7-9n | | 4b+8=7b-4 | | -6f=-36 | | 3x-1=5x+7 | | 15a-10=20a | | (2/5)+x=(-1/10) | | -6(18+3y)=-9 | | (2n+2)(2n-2)= | | 14x-(10x-3)=17 | | (2/5)+=(-1/10) | | 13+(-15x)=74-12 | | (2n^2+2)(2n-2)= | | 2n+7n-28=26 | | 12x-5x=49 | | 12=3t | | 3xy+5x+2xy-8x= | | 14=2p | | 2/3(n-3)=1/3(n+6) | | 12(3x+4)-7=2x-23 | | ln(x)+ln(2)=3 | | -(-9x)=(-48) | | 5-4m-5m=m-4m+2 | | 6x-4y+x-5y= | | y=.5x-4 | | 14=2b |

Equations solver categories